Supporting women's career advancement - Burke, Ronald J.; Vinnicombe, Susan (Women in management review, 2006)
An e-book that addresses some of the issues still facing women in the development and advancement of their managerial careers. Inspite of women's parity in higher education and initial success in achieving work experiences they still fall behind in numbers when it comes to senior executive jobs. Three of the papers explore the barriers that still exist and another two look at how women do succeed in advancement. The last paper looks at how women use role models. Together these papers provide a balanced picture of the barriers still facing women managers and the enablers which are helping women.